Origin of the 2D Electron Gas at the SrTiO3 Surface. Issue 24 (16th May 2022) - Yan, Xi; Wrobel, Friederike; Tung, I‐Cheng; Zhou, Hua; Hong, Hawoong; Rodolakis, Fanny; Bhattacharya, Anand; McChesney, Jessica L.; Fong, Dillon D.
Abstract: Bulk SrTiO3 is a well‐known band insulator and the most common substrate used in the field of complex oxide heterostructures. Its surface and interface with other oxides, however, have demonstrated a variety of remarkable behaviors distinct from those expected. In this work, using a suite of in situ techniques to monitor both the atomic and electronic structures of the SrTiO3 (001) surface prior to and during growth, the disappearance and re‐appearance of a 2D electron gas (2DEG) is observed after the completion of each SrO and TiO2 monolayer, respectively. The 2DEG is identified with the TiO2 double layer present at the initial SrTiO3 surface, which gives rise to a surface potential and mobile electrons due to vacancies within the TiO2− x adlayer. Much like the electronic reconstruction discovered in other systems, two atomic planes are required, here supplied by the double layer. The combined in situ scattering/spectroscopy findings resolve a number of longstanding issues associated with complex oxide interfaces, facilitating the employment of atomic‐scale defect engineering in oxide electronics. Abstract : The 2D electron gas at the surface of SrTiO3 (001) can be turned on and off by depositing either SrO or TiO2, which is observed by a combination of oxide molecular beam epitaxy with in situ synchrotron X‐ray scattering and angle‐resolved photoemission spectroscopy. Either way, the surface remains TiO2 ‐terminated.